1970
DOI: 10.1007/bf01262581
|View full text |Cite
|
Sign up to set email alerts
|

Electron optical studies of bovine viral diarrhea-mucosal disease virus (BVDV)

Abstract: After concentration and purification steps involving ultracentrifugation, density gradient centrifugation in potassium tartrate and rate zonal centrifugation in saccharose the virus of bovine virus diarrhea-mucosal disease of cattle (strain Oregon C24 V) was studied electron microscopically. The virion consists of an envelope without projections and a nucleocapsid probably displaying a cubical symmetry. The particle has a diameter of 57 • 7 m~z the core accounting for 24 q-4m~z.The morphological relationship t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Polymorfism of the virions, similar to what was observed in the present study has been reported for rubella virus (5,19) and lactic dehydrogenase elevating virus (1, 4,33,41). It has been argued that this pleomorfism represents artifacts caused by preparation (4,16) rather than true forms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Polymorfism of the virions, similar to what was observed in the present study has been reported for rubella virus (5,19) and lactic dehydrogenase elevating virus (1, 4,33,41). It has been argued that this pleomorfism represents artifacts caused by preparation (4,16) rather than true forms.…”
Section: Discussionsupporting
confidence: 91%
“…This has revealed a wide range in particle size, the estimations ranging from 35 to more than 100 nm (14,15,17,19,34,40). This has revealed a wide range in particle size, the estimations ranging from 35 to more than 100 nm (14,15,17,19,34,40).…”
Section: Introduetionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies of BVDV in thin sections have been made by Ritchie & Fernelius (1969) and Ohmann & Bloch (1982) who described BVDV virus as spherical particles approximately 50 nm in diameter. Most studies of BVDV have utilized suspensions of virus and negative staining (Hafez et al, 1968;Maess & Retzko, 1970;Horzinek et al, 1971 ;Stott et al, 1974;Chu & Zee, 1984), and have variously reported the virus as roughly spherical and from 30 to 100 nm or more in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Examination by eteetron microscopy of negatively stained virus preparations has revealed a variety of generally undistinguished structures (4,8,9,11,16). Although these might represent enveloped togavirus particles, whose morphology is ill-defined in this type of preparation, the reported size range of 30--100 nm is large.…”
Section: Discussionmentioning
confidence: 99%